2019
DOI: 10.1101/781104
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative transcriptome analysis of the ovary and testis of the lacustrine goby (Gobiopterus lacustris)

Abstract: ABSTRCTLacustrine goby (Gobiopterus lacustris) belongs to a genus of gobies that are small in size and endemic to freshwater, brackish waters or coastal environments around the Indian and Pacific oceans. To date, there are no genomic or transcriptomic studies on G. lacustris. Here, we constructed gonadal transcriptomes of G. lacustris for the first time and identified genes that may be involved in gonadal development and reproduction. In total, 60,657,644 and 52,016,136 clean reads were obtained from ovary and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 73 publications
1
1
0
Order By: Relevance
“…The differences in the morphology of male and female fish can be seen in Figure 2. This is in accordance with the statement of Dong et al (2019), that gobiopterus fish can be differentiated by sex through their morphological characteristics. Observation of fish sexual dimorphism can be done by observing the shape of the caudal fin, body shape, and body abdominal shape.…”
Section: The Morphology Of Lempuk Fishsupporting
confidence: 92%
“…The differences in the morphology of male and female fish can be seen in Figure 2. This is in accordance with the statement of Dong et al (2019), that gobiopterus fish can be differentiated by sex through their morphological characteristics. Observation of fish sexual dimorphism can be done by observing the shape of the caudal fin, body shape, and body abdominal shape.…”
Section: The Morphology Of Lempuk Fishsupporting
confidence: 92%
“…However, there is little information on the tissue‐specific role of CYP27 in fish. The newest finding has shown that cyp27a1 is highly expressed in the sexually mature testis of the lacustrine goby ( Gobiopterus lacustris ), and cyp27c1 is highly expressed in the ovary (Dong et al, 2021). As for cyp46a1, it has been demonstrated that its encoded enzyme is responsible for cholesterol elimination from the brain in hamster (Mast et al, 2010) and cavefish (Meng, Wang, et al, 2018; Meng, Zhao, et al, 2018).…”
Section: Discussionmentioning
confidence: 99%